2020
DOI: 10.1186/s13063-020-04324-z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic pillbox-enabled self-administered therapy versus standard directly observed therapy for tuberculosis medication adherence and treatment outcomes in Ethiopia (SELFTB): protocol for a multicenter randomized controlled trial

Abstract: Background: To address the multifaceted challenges associated with tuberculosis (TB) in-person directly observed therapy (DOT), the World Health Organization recently recommended that countries maximize the use of digital adherence technologies. Sub-Saharan Africa needs to investigate the effectiveness of such technologies in local contexts and proactively contribute to global decisions around patient-centered TB care. This study aims to evaluate the effectiveness of pillbox-enabled self-administered therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 83 publications
0
41
0
2
Order By: Relevance
“…The SELFTB Trial included 10 public health centers with the largest TB client load. The average quarterly cases in the sites [14] have been reduced by two-third in the COVID-19 period.…”
Section: Covid-19 Implications On Tb Carementioning
confidence: 96%
See 2 more Smart Citations
“…The SELFTB Trial included 10 public health centers with the largest TB client load. The average quarterly cases in the sites [14] have been reduced by two-third in the COVID-19 period.…”
Section: Covid-19 Implications On Tb Carementioning
confidence: 96%
“…We see a similar challenge in Addis Ababa where we have sites for both EXIT-TB study and the SELFTB Trial (Electronic pillbox-enabled self-administered therapy versus standard directly observed therapy for tuberculosis medication adherence and treatment outcomes in Ethiopia: a multicenter randomized controlled trial) [14]. The SELFTB Trial included 10 public health centers with the largest TB client load.…”
Section: Covid-19 Implications On Tb Carementioning
confidence: 99%
See 1 more Smart Citation
“…Glossary of research terms in the review.Glossary DescriptionBiomarker A measurable characteristic of the organism state during treatment18 Treatment completedTreatment completed as recommended by the national policy8 Predictive biomarkersBiomarkers which allow the prediction of the treatment outcome 10 Bacterial loads A measure of M. tb in original sputum samples and quantified as estimated colony-forming unit in 1 mL of sputum sample (eCFU/mL)18,19 Xpert MTB/RIF Molecular method for diagnosis of TB and can provide resistance strain on rifampicin14,15 TB: tuberculosis.…”
mentioning
confidence: 99%
“…However, compared to other countries, it is still much lower. Africa, in general, shares only 2.4% of clinical trials generated globally and Ethiopia shares only 2.3% of clinical trials generated out of Africa and the trials are limited in number and variety ( 13 – 15 ). This is due to the existence of many challenges for the conduct of clinical trials that would determine the safety and efficacy of new products and interventions in the country.…”
Section: Introductionmentioning
confidence: 99%